DISTANCE- DEPENDENT COMPETITION INDICES FOR PREDICTING GROWTH OF Pinus brutia TEN. TREES IN ZAWEETA REGION (Mesopotamia Journal of Agriculture)
Pine is one of the prevalent trees in Zawita forest and a grows naturally on the mountain slopes, to study the competition and spatial analysis in a forest of Zawita, (13) samples were taken from areas of dimensions (60 X 60) m, at each samples, measurements of the past five years growth were taken , regression models for each of growth in diameter ( ∆D ) and basal area ( ∆BA ). It become clear that change in diameter ( ∆D ) showed in many of spaces different from the subject tree and the highest correlation at the distance (3-30)m and it indicates that increase in the total basal area of trees adjacent to subject tree has led to increase the link, which indicates the existence of competition between the subject tree and other trees, change in basal area of subject tree( ∆BA ). We note a correlation between it and basal area of trees adjacent at different distance and increasingly concentric, it seemed that there is a correlation highly, used as evidence competition between the change in diameter of subject tree and the total basal area at many of concentric circles and reached maximum at two circles ( 9-18 )m and ( 9-15 )m .